Inhibition of Glutaminase 1 Reduces M1 Macrophage Polarization to Protect Against Monocrotaline-Induced Pulmonary Arterial Hypertension - Xing Chen; Lixiang Li; Yan Deng; Juan Liao; Hui Meng; Limei Liang; Jie Hu; Dongwei Xie; G Liang (2025)
(1) BACKGROUND: Metabolic abnormalities and immune inflammation are key elements within pathogenesis of pulmonary arterial hypertension (PAH). And in PAH patients, aberrant glutamine metabolism has been observed; however, the function of glutaminase 1 (GLS1) in macrophage is still unknown. So we aims to investigate GLS1's impact upon macrophages in PAH. (2) METHODS: We firstly constructed an monocrotaline (MCT)-induced PAH rat model. Briefly, the PAH rats were treated with the GLS1 inhibitor BPTES, and various index were evaluated, including hemodynamics, right ventricular function, pulmonary vascular remodeling, macrophage markers, and glutamine metabolism. After that, we polarized bone marrow-derived macrophages (BMDMs) into M1 phenotype and then subjected to BPTES intervention. Finally, we assessed macrophage phenotype, inflammatory markers, and glutamine metabolism indicators, along with the impact of BMDM supernatant on the behavior of pulmonary arterial smooth muscle cells (PASMCs). (3) RESULTS: GLS1 was significantly upregulated in both PAH patients and rats. Treatment with the GLS1 inhibitor BPTES markedly improved pulmonary arterial pressure, right ventricular function, and pulmonary vascular remodeling in PAH rats, while inhibiting M1 macrophage polarization, NLRP3 activation, and the release of pro-inflammatory cytokines. This, in turn, alleviated the proliferation and migration of PASMCs induced by inflammatory stimuli. (4) CONCLUSION: We propose that targeting GLS1 to reduce M1 macrophage polarization and inflammatory responses may represent a promising therapeutic approach for PAH.